A spatial accessibility framework for mapping the mismatch between wood supply and demand across Europe - Anita Poturalska; Ossi Kotavaara; Terhi Ala-Hulkko (Ecological Indicators)
Wood is one of the most important provisioning ecosystem services (ES) of forest, crucial for maintaining the welfare and wellbeing of the population. This study maps the spatial mismatches between wood ES supply and demand across the European continent, using the concept of ES spatial flow. We first examine how balanced the relationship between wood ES supply and demand is within the region, using overlay analysis. We then test how the balance changes when applying the spatial flow of wood ES at different transport distances, using the spatial accessibility methodology. Our findings reveal that Europeans have good spatial accessibility to wood resources produced across the continent when considering spatial flows of services. Approximately 65% of demand can be met in Europe without considering spatial flows, due to the abundance of wood resources. However, interregional transport needs to be included in the analysis to fully meet European demand. This illustrates how provisioning ES spatial flow can be effectively incorporated in evaluation of ES mismatches. We suggest that spatial accessibility methods and the concept of ES spatial flow can be used to increase understanding of the balance between supply and demand, as well as issues related to the sustainable use of ES and ecosystems exploitation in the future.